Binding non-signatories to arbitration agreements—who are persons 'claiming through or under' a party?. (25th October 2019) - Priskich, Vicky
Abstract: The International Arbitration Acts of the UK, Australia, Singapore, and Hong Kong recognize that third persons who are non-signatories to an arbitration agreement but who are 'claiming through or under' a party to the arbitration agreement have the status of a party. 1 In the UK and Singapore that status means not only that court proceedings involving such non-signatories may be stayed in favour of arbitration but it also binds them to an award. In Hong Kong that status binds non-signatories to an award. In Australia, that status affects whether court proceedings involving non-signatories are stayed in favour of arbitration. A recent judgment by a majority of Australia's highest appeal court, the High Court of Australia, in Rinehart v Hancock Prospecting Pty Ltd 2 has taken a different approach to that prevailing in England as to the range of persons who are capable of 'claiming through or under' a party to the arbitration agreement, thereby significantly expanding the range of disputes involving non-signatories that must be referred to arbitration. 3 The issue has not arisen for determination before appellate courts in Singapore or Hong Kong. Rinehart therefore represents an important development in common law jurisdictions, compelling arbitration between a signatory and non-signatory to an arbitration agreement.